WIDJOJONOMICS SAMPAI HABIBIENOMICS - Fajar Nur Alam; Farida Sarimaya (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
This article entitled “Widjojonomics to Habibienomics: Different views of Economic thoughts of Widjojo Nitisastro and B.J Habibie towards Indonesian Economy in the New Order.” The main issues raised in this study is how differing ideas of B.J Habibie and Nitisastro Widjojo about Indonesian economy in the New Order era in 1971-1999. The method used in this bachelor thesis research is historical method, which is conducted in following steps: heuristics, criticism, interpretation, and historiography, while the technique used is literature study. Based on the study, several conclusions can be drawn. The government of New Order started its governance with economic crisis. To solve it, therefore stabilization and rehabilitation of national economy is needed. Widjojo Nitisastro and B. J. have different background both in terms of their youth life and education. That is what influences the characters and ways of their thinking. Economic principal of Widjojo Nitisastro, which often called as Widjojonomics, exemplifies that modernization of economic system that covers market, fiscal and foreign debt is expected to give birth to a trickle-down effect, which assumes that if the policy is intended to provide benefits for the rich, the poor would also be impacted through the employment expansion, income distribution and market expansion.  Economic principal of B.J Habibie, which often called as Habibienomics, is a system of economy that should be developed though the seizure of advanced technology to catch up with developed countries. Indonesia should not only be a state that can only produce goods that have comparative advantages. Instead, Indonesia should also have added value and competitive advantage.